2019
DOI: 10.1097/acm.0000000000002503
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Development in Postgraduate Medical Education: A Systematic Review of the Literature

Abstract: CanMEDS is an initiative to improve patient care by enhancing physician training and practice. From its beginning in the 1990s, its main purpose has been to articulate a comprehensive definition of the competencies that physicians need to deliver high-quality patient care. These competencies are now well established in the Royal College's training standards. In 2012, the Royal College began a multi-year review and update of the CanMEDS 2005 Physician Competency Framework. As part of the CanMEDS 2015 project, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 50 publications
0
68
0
1
Order By: Relevance
“…Comprehensive reviews on leadership education have noted an over-emphasis on cognitive and intellectual-related leadership competencies, without enough attention to the domains of character and emotional intelligence development. 5 It is encouraging to see that pediatric program directors identified a balanced set of leadership skills as high-value, in keeping with recent educational calls to action.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 85%
See 1 more Smart Citation
“…Comprehensive reviews on leadership education have noted an over-emphasis on cognitive and intellectual-related leadership competencies, without enough attention to the domains of character and emotional intelligence development. 5 It is encouraging to see that pediatric program directors identified a balanced set of leadership skills as high-value, in keeping with recent educational calls to action.…”
Section: T a G G E D H 1 Discussiont A G G E D E N Dmentioning
confidence: 85%
“…Comprehensive reviews of current educational practices in leadership in medicine have found variability in content, teaching modalities, and evaluation strategies. 5,6 The lack of a shared conceptual framework makes it challenging for residency programs to develop new content or expand upon existing leadership education programs. Existing heterogeneity across curricula complicates comparative analyses, limiting the evaluation of the longitudinal impact of leadership training.…”
Section: T a G G E D P What's Newmentioning
confidence: 99%
“…Additionally, leaders of all residency programs should begin to incorporate formal leadership development into the curriculum and consider adding leadership as a core competency in our training. 3,4 You have selected us into your programs, and we have proven to you our leadership potential, now we ask you to help us become the leaders our patients and our hospitals need.…”
Section: Lucy LI Mdmentioning
confidence: 99%
“…2 These pedagogical methods can incorporate didactic, theoretical learning, interactive discussion, self-reflection exercises, mentorship/coaching, experiential (direct placement in a leadership setting or role), and project-based deliverables to the larger health system. 3 However we choose to accomplish our goal of preparing our learners and faculty to be engaged health systems leaders, we must start now. The legacy of leadership in family medicine within an embattled health care system is likely of greater importance now than ever.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] As such, the need for ongoing leadership education and training is increasingly recognized. [19][20][21][22][23][24][25] The call to action 1,2,[25][26][27][28] to increase formal and comprehensive leadership training for physicians is not a new one, and leadership training opportunities for physicians within academic health centers are increasingly common. 27 However, a recent systematic review 27 highlighted that current programming more often focuses on broader leadership competencies (e.g., leadership style, feedback), with only a minority of programs covering specific skillsets, such as those skills involved in running an effective team meeting (e.g., group facilitation, group problemsolving and decision-making, oral presentation skills, coaching skills to address specific behaviors).…”
Section: Introductionmentioning
confidence: 99%